2002
DOI: 10.1177/000331970205300417
|View full text |Cite
|
Sign up to set email alerts
|

Venous Aneurysms of the Upper Extremity

Abstract: Venous aneurysms are a rare clinical entity, especially in upper extremities. A 35-year-old Japanese woman was diagnosed as having venous aneurysms in her left arm. The lesions were excised, and microscopic examination revealed a lack of smooth muscle, media, and elastic fibers in the aneurysmal wall, with partial hyperplasia of smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Many studies mentioned the rarity of primary superficial VAs. 2,3 A study about primary VA showed that, 4.77% of the VAs were located in the lower extremities and most of them were in the deep venous system; 10% were located in the upper extremities. 4 To date only 17 reports of superficial VAs of upper extremities have been published in the English language literature and just one case described radial nerve compression induced by a cephalic VA. 2,5 The aetiology of VA remains unclear, although several theories have been elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies mentioned the rarity of primary superficial VAs. 2,3 A study about primary VA showed that, 4.77% of the VAs were located in the lower extremities and most of them were in the deep venous system; 10% were located in the upper extremities. 4 To date only 17 reports of superficial VAs of upper extremities have been published in the English language literature and just one case described radial nerve compression induced by a cephalic VA. 2,5 The aetiology of VA remains unclear, although several theories have been elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial venous aneurysms of the upper extremity or neck are rare, and, to our knowledge, only 26 reports have been published in the English language literature (17 cases, upper extremity; 8 cases, external jugular vein; and 1 case, anterior jugular vein). [5][6][7][8] In comparison with superficial venous aneurysms, deep venous aneurysms of the extremity or neck are relatively common. Initially, most superficial venous aneurysms were misdiagnosed as subcutaneous soft tissue tumors, lymphoceles, hygromas, varicose veins, hemangiomas, arteriovenous fistulas, or inguinal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…21 Superficial venous aneurysms are usually well managed by simple ligation and excision. 6 Moreover, small saphenous venous aneurysms can be treated both by endoluminal laser and by endovenous radio frequency energy, although endovenous ablation may be desirable in the presence of a large venous aneurysm. 13 Venous dilatation and large varices could be treated with injections of foam and sclerosing agents, followed by local compression, which obliterates or thromboses the aneurysmal space; however, the use of foam-sclerotherapy to obliterate venous aneurysms has been reported in only 2 cases.…”
Section: D a Bmentioning
confidence: 99%
“…5 Second, it can appear in various parts of the body. 5,6 Third, it is found as a localized lesion of vein segment, which is not associated with prolongation of the affected vein. 6 Unlike secondary type, the etiology of primary type remains unknown.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 Third, it is found as a localized lesion of vein segment, which is not associated with prolongation of the affected vein. 6 Unlike secondary type, the etiology of primary type remains unknown. However, several hypotheses, such as endophlebohypertrophy, which means dilatation of vein wall followed by early hypertrophy, and congenital weakness or degenerative changes due to tissue alteration, had been introduced.…”
Section: Discussionmentioning
confidence: 97%